Analysis of Mathematical Literacy on Students' Metacognition in Conic Section Material. (December 2019) - Salsabila, E; Rahayu, W; Kharis, S A; Putri, A
Abstract: Mathematical literacy is one of the components that use mathematical concepts and applies them to an everyday situation. Mathematical literacy helps people to identify and understand the role that mathematics plays in the world, and to make the well-founded judgments and decisions required in life by constructive, engaged, and reflective citizens. By contrast, not everybody acquires sufficiently. This study aims to describe the ability of mathematical literacy especially geometry literacy in terms of student metacognition on conic section material. The problems in this study were: 1) How is the ability of mathematical literacy in terms of student metacognition on conic section material 2) What types of mistakes do students make in solving the problem of cone section and 3) What factors cause students to make mistakes in solving conic section question. This research is a qualitative descriptive study. The subjects in this study were 36 mathematics education students who took courses in Analytical Geometry. The data collected using observation, written test, and interview. Before the researcher conducted the analysis, the researcher examined the validity of the data using validity and reliability tests in order to obtain valid data. Furthermore, the valid data were analysed descriptively through identification, grouping, clarification, explanation and conclusion.